(untitled) (African Disability Rights Yearbook, 2024)
As one of the first signatories to the United Nations Convention on the Rights of Persons with Disabilities (CRPD) and having ratified it on 7 July 2010, Ethiopia is committed to ensuring the rights and well-being of people with disabilities. Nine years after ratifying the CRPD, in 2019, it issued a new electoral law (Electoral, Political Parties Registration and Election’s Code of Conduct Proclamation (Proclamation)). However, this new Electoral Proclamation is not in compliance with the CRPD in terms of polling accessibility, accessible voting procedures, and the removal of disability based voting restrictions. Even worse, in terms of discrimination based on psycho-social and intellectual (mental) disability, the Proclamation contravenes the CRPD to a greater extent than legislation that was passed decades before the coming into force of the CRPD, despite being enacted after its ratification. The primary focus of this article is, therefore, to examine the discrepancy between the voting provisions in the Proclamation and the minimum voting standards set forth in the CRPD. The goal is to demonstrate the gaps in the Proclamation that may prevent persons with disabilities from fully participating in the voting process.